Modelling and validation of Eddy current response to changes in factors affecting pressure tube to calandria tube gap measurement. (July 2015) - Shokralla, Shaddy; Sullivan, Sean; Morelli, Jordan; Krause, Thomas W.
Abstract: Procedures employed to non-destructively examine nuclear power plants must undergo inspection qualification to ensure that they meet their respective inspection specification requirements. Modelling is a powerful tool that can be exploited in the inspection qualification process. The gap between pressure tubes (PTs) and calandria tubes (CTs) in CANDU (CANada Deuterium Uranium) fuel channels is periodically measured, as contact can result in localized cooling and potential cracking. This work shows how an analytical model can be employed to characterize the effects of PT wall thickness and resistivity variation on gap measurement, and details its validation against physical experiments. Abstract : Highlights: Gap for pressure tubes within calandria tubes in CANDU nuclear reactors is required. Eddy current response to gap variation modeled analytically via Dodd and Deeds equations. Pressure tube wall thickness and resistivity variation on EC response modeled. Quantitative agreement between analytic model and physical experiments obtained. Application of modelling EC for qualification of inspection procedures discussed.